2022
DOI: 10.3389/fmicb.2022.1039040
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle-mediated regulation of macrophage polarization in bacterial infections

Abstract: Extracellular vesicles (EVs) are nanoscale membrane-enveloped vesicles secreted by prokaryotic and eukaryotic cells, which are commonly defined as membrane vesicles (MVs) and exosomes, respectively. They play critical roles in the bacteria–bacteria and bacteria–host interactions. In infectious diseases caused by bacteria, as the first line of defense against pathogens, the macrophage polarization mode commonly determines the success or failure of the host's response to pathogen aggression. M1-type macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 157 publications
0
13
0
Order By: Relevance
“…Interestingly our analyses also indicated that uninfected bystander cells were directly contributing to inflammation despite not being actively infected with AIEC. It is likely that immune activation of these bystander cells is driven by either contact with bacteria, bacteria- derived molecules and vesicles being shed into the media, or immune cell derived TNFα (Bringer et al ., 2012; Jung et al ., 2017; Qu, Zhu and Zhang, 2022). However, the relative contribution of each to bystander cell activation cannot be ascertained from the data generated here, but understanding this could be informative in the context of CD given the importance of TNFα in driving inflammation in CD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly our analyses also indicated that uninfected bystander cells were directly contributing to inflammation despite not being actively infected with AIEC. It is likely that immune activation of these bystander cells is driven by either contact with bacteria, bacteria- derived molecules and vesicles being shed into the media, or immune cell derived TNFα (Bringer et al ., 2012; Jung et al ., 2017; Qu, Zhu and Zhang, 2022). However, the relative contribution of each to bystander cell activation cannot be ascertained from the data generated here, but understanding this could be informative in the context of CD given the importance of TNFα in driving inflammation in CD.…”
Section: Discussionmentioning
confidence: 99%
“…They contain immunomodulatory molecules that can target host innate immune pattern recognition receptors (PRR) such as Toll-like receptors (TLRs) and Nod-like receptors (NLRs) signaling pathways, thereby stimulating the release of pro-inflammatory cytokines and chemokines, which attract immune cells to the site of inflammation. 114 As a result of the small sizes of MVs and their immunogenicity, their interaction with innate immune cells (macrophages and neutrophils), antigen-presenting cells 115 (dendritic cells), and/or adaptive immune cells (T- and B- cells), leads to the generation of various immune responses as illustrated in Figure 5 . 115 , 116 For instance, the detection of LPS and LOS by TLR-4 results in the activation of nuclear factor-kappa B (NF-κB) and the release of proinflammatory cytokines.…”
Section: Overview Of Mvsmentioning
confidence: 99%
“…Although the exact functions of macrophages will differ depending on location and task at hand, based on their functional program, macrophages are divided into pro-inflammatory [M1, classically activated (AM)], mainly involved in anti-pathogen and anti-tumor responses, and clearing debris, and the anti-inflammatory [M2a-d, alternatively activated (AAM)] macrophages, responsible for tissue repair and regeneration, angiogenesis, and parasite containment ( 29 , 30 , 31 ). M1 are induced by T helper cells type 1 (TH1) cytokines, such as interferon gamma (IFNγ), interleukin (IL)-2, IL-10, and tumor necrosis factor (TNF)-α/β, and produce proinflammatory cytokines, reactive oxygen species (ROS), and inducible nitric oxide synthase (iNOS).…”
Section: Types Of Macrophagesmentioning
confidence: 99%